Bioinspired Nanotechnology: Biologically Inspired, Cell‐Selective Release of Aptamer‐Trapped Growth Factors by Traction Forces (Adv. Mater. 7/2019). Issue 7 (12th February 2019) - Stejskalová, Anna; Oliva, Nuria; England, Frances J.; Almquist, Benjamin D.
Abstract : In article number1806380, Benjamin D. Almquist and co‐workers describe a bioinspired nanotechnology platform that uses the cellular traction force as a trigger for controlling the release of growth factors. This method of release is straightforward to integrate with diverse biomaterial scaffolds, substrates, and fabrication methods, and enables novel capabilities like the selective activation of growth factors by different cell types.